Employment of an Autonomous Underwater Vehicle as mobile bridge among heterogeneous acoustic nodes. Issue 1 (July 2017) - Allotta, Benedetto; Ridolfi, Alessandro; Bianchi, Matteo; Fanelli, Francesco; Gelli, Jonathan; Monni, Niccolò; Nocciolini, Daniele; Pagliai, Marco; Paolucci, Libero; Pecorella, Tommaso
Abstract: Nowadays, underwater acoustic communication is an interesting topic of research. This is especially true in the case of Autonomous Underwater Vehicles (AUVs): due to the limitations of underwater environment, where wireless and radio communications are not possible, it is very important to possess efficient and reliable tools for acoustic data exchange. Indeed, an underwater network of acoustic nodes can enhance the navigation and localization capabilities of one or more vehicles. In this paper, the authors investigate the use of an AUV as a mobile bridging node within a network of fixed heterogeneous acoustic modems. In particular, MARTA AUV, developed and built by the Department of Industrial Engineering (DIEF) of the University of Florence is employed in order to enable data transmission between modems of different manufacturers. Suitable bridging tests, whose results are proposed in this paper, were executed in order to evaluate the feasibility of such approach, showing that AUVs can efficiently accomplish the role of gateway between the nodes of the network.